Secondary chronic cluster headache treated by posterior hypothalamic deep brain stimulation: First reported case. (January 2013) - Messina, Giuseppe; Rizzi, Michele; Cordella, Roberto; Caraceni, Augusto; Zecca, Ernesto; Bussone, Gennaro; Franzini, Angelo; Leone, Massimo
Introduction: Deep brain stimulation (DBS) of the posterior hypothalamus (pHyp) has been reported as an effective treatment for primary, drug-refractory and chronic cluster headache (CCH). We here describe the use of such a procedure for the treatment of secondary CCH due to a neoplasm affecting the soft tissues of the right hemiface. Methods: A 27-year-old man affected by infiltrating angiomyolipoma of the right hemiface who subsequently developed drug refractory homolateral CCH underwent DBS of the right pHyp region at the Fondazione IRCCS Istituto Nazionale Neurologico Carlo Besta. Results: After surgery, the patient presented a significant reduction in frequency of pain bouts. However, because of a subsequent infection, the entire system was removed. After re-implantation of the system, successful outcome was observed at 2 years follow-up. Discussion: This brief report shows the feasibility of pHyp DBS in secondary drug-refractory CCH syndromes; future reports are needed in order to confirm our positive result.